2024
DOI: 10.3390/pr12010109
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Influence of Ion Channels on the Healing of Skin Wounds in Rats

Alexandra Grigore,
Ana Vatasescu-Balcan,
Smaranda Stoleru
et al.

Abstract: At the level of skin wounds, an electrical potential difference develops between the edges of the wound and the center of the wound, which favors the migration of cells in the process of their healing. Cells migrate in an electric field because they have a certain electrical membrane potential. This potential is due to differences in the transmembrane electrochemical gradient. The transmembrane electrochemical gradient is due to the migration of sodium, potassium, and calcium ions into the corresponding ion ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In a recent study of our research team, it was demonstrated that blocking potassium channels leads to wound healing. Since the potassium current is a depolarizing current, while the calcium and sodium currents are repolarizing, the blocking potassium current increases the membrane potential, which is counteracted by blocking the calcium and sodium currents [ 83 , 84 ].…”
Section: Topics In Wound Healingmentioning
confidence: 99%
“…In a recent study of our research team, it was demonstrated that blocking potassium channels leads to wound healing. Since the potassium current is a depolarizing current, while the calcium and sodium currents are repolarizing, the blocking potassium current increases the membrane potential, which is counteracted by blocking the calcium and sodium currents [ 83 , 84 ].…”
Section: Topics In Wound Healingmentioning
confidence: 99%
“…In a recent study of our research team, it has been demonstrated that blocking potassium channels leads to wound healing. Since potassium current is a depolarizing current, while calcium and sodium currents are repolarizing, blocking potassium current increases the membrane potential, which is counteracted by blocking calcium and sodium currents [76,77].…”
Section: Wound Healing and Endogenous Electric Fieldsmentioning
confidence: 99%